Сільськогосподарські машини вітчизняного виробництва для реалізації систем ґрунтозахисних та енергоощадних технологій - Сало, В. М.; Лещенко, С. М.; Богатирьов, Д. В.; Лещенко, С. Н.; Богатырев, Д. В.; Salo, V.; Leshchenko, S.; Bohatyrev, D. (ЦНТУ, 2017)
Цього року кафедрі сільськогосподарського машинобудування Центральноукраїнського національного технічного університету виповнюється 120 років. З цієї нагоди матеріал даної статті містить інформацію про внесок науковців кафедри в розвиток агропромислового комплексу України з представленням розроблених та впроваджених у виробництво в останні роки деяких зразків сучасних сільськогосподарських машин. В роботі доводиться необхідність розробки та провадження у виробництво вітчизняних сільськогосподарських машин, наголошується на тому, що поступове впровадження запропонованої техніки в технологічні процеси вирощування сільськогосподарських культур має стати базисом для впровадження ґрунтозахисних та енергоощадних технологій. Описані конструктивні особливості та вказані переваги використання у різних ґрунтово-кліматичних умовах подрібнювачів рослинних решток, комбінованих чизельних глибокорозпушувачів, універсальних культиваторів, парових культиваторів та ланцюгових борін. В этом году кафедре сельскохозяйственного машиностроения Центральноукраинского национального технического университета исполняется 120 лет. По этому случаю материал данной статьи содержит информацию о вкладе ученых кафедры в развитие агропромышленного комплекса Украины с представлением разработанных и внедренных в производство в последние годы некоторых образцов современных сельскохозяйственных машин. В работе оказывается необходимость разработки и внедрения в производство отечественных сельскохозяйственных машин, отмечается, что постепенное внедрение предлагаемой техники в технологические процессы выращивания сельскохозяйственных культур должна стать базисом для внедрения почвозащитных и энергосберегающих технологий. Описаны конструктивные особенности и указаны преимущества использования в различных почвенно-климатических условиях измельчителей растительных остатков, комбинированных чизельных глубокорыхлителей, универсальных культиваторов, паровых культиваторов и цепных борон. In the last few years Ukraine was filled with non-traditional and in some cases unknown technologies of crop science. The changes started by using imported harvesters which left practically all residues on the field. This practice allowed increasing the productivity of picking processes and shortening the terms of harvest period but there appeared the problem of plant residues further processing. The Ukrainian producers chose the simplest way to solve it and used disc equipment for soil cultivation. As a result, the structure of surface soil was damaged, valuable agro-technical aggregates were mashed, which led to their transformation into dusty unstructured condition. There was also over-tamping of subsoil, dysfunction of the aeration and infiltration processes, decrease of the storage of productive soil water in lower levels. This year the Department of Agricultural Engineering of Central Ukrainian National Technical University celebrates its 120th anniversary. On this occasion, the article contains the information on the contribution of the scientists of the department to the development of the agro-industrial complex of Ukraine by the introduction of some models of modern agricultural machines. They were developed and launched within recent years. The article shows the necessity of development and production of home-made agricultural machines. It is highlighted that the gradual introduction of the suggested machines into the technological processes of growing crops should become the basis for the introduction of soil protective and energy-saving technologies. The design features and the advantages of using plant residues shredders, combined chisel deep-tillers, universal cultivators, field cultivators and chain harrows in different soil and climatic conditions have been described. The presented designs of machines were introduced into production and have been operating successfully on the fields of many agrarian companies. They provide high productivity and quality of technological processes confirming the efficiency and reliability of the design and significant cost savings compared with the purchase of foreign machines of similar application. Systematic launch of the developed technology into the technological processes of cultivation, timely operations and the refusal of the application of erosion-hazardous equipment can serve as the basis for the implementation of systems of soil protection and energy-saving technologies. We hope that our elaborations will improve the overall efficiency of agricultural production, promote the preservation and restoration of soil fertility and high yields.
Сельскохозяйственные машины отечественного производства для реализации систем почвозащитных и энергосберегающих технологий
National agricultural machines for the systems of soil-protecting and energy-saving technologies
Keywords: ґрунтозахисні та енергоощадні технології; подрібнювач рослинних решток; комбінований чизельний глибокорозпушувач; універсальний культиватор; ланцюгова борона; почвозащитные и энергосберегающие технологии; измельчитель растительных остатков; комбинированный чизельный глубокорыхлитель; универсальный культиватор; цепная борона; soil-protecting and energy-saving technologies; plant residues shredder; combined chisel deep-tiller; universal cultivator; chain harrow